Effects of cooperative and problem-solving learning strategies on students’ achievement in senior secondary school history in Oyo State (2016)
The increasing and fluctuating level of poor performance of students in History calls for a need to ascertain students’ learning strategies that promote achievement in the subject. This study investigated the effect of learning strategies as determinants of achievement in History. The study adopted a non-randomised pre-test posttest control group quasi-experimental design using 3x2x2 factorial design. Multi-stage sampling technique was used and data were collected from 184 SSS II History students from 18 public senior secondary schools in Oyo State. Seven hypotheses guided the study and four instruments were used for data collection with reliability coefficients of 0.74 for HAT, 0.72 for LSI, 0.75 for HIG and 0.75 for SHI. Data were analysed using Analysis of Covariance. Results indicated that cooperative and problem-solving learning strategies had significant main effect on students’ achievement in History, F (2,171) = 63.19 with partial eta square of 0.43; learning style has significant main effect on students’ achievement, F (1,171) = 11.84 with partial eta square of 0.07; Learning strategies, learning styles and study habit had no significant interaction effect on students’ achievement. Learning is internalised faster and better when students are given opportunity to interact with one another in small groups; when topics are structured to solve real life problems, studying becomes fun and learning is facilitated and internalised; students learn better when a problem is used as a starting point for new knowledge and adjustment of instructional strategies will enhance achievement in History.